Antiangiogenic and anti-invasive effects of sunitinib on experimental human glioblastoma - de Boüard, Sophie (Duke University Press, 2007)
Angiogenesis inhibitors appear to be promising therapies for highly vascularized tumors such as glioblastoma multiforme (GBM). Sunitinib is an oral multitargeted tyrosine kinase inhibitor with both antiangiogenic and antitumor activities due to selective inhibition of various receptor tyrosine kinases, including those important for angiogenesis (vascular endothelial growth factor receptors and platelet-derived growth factor receptors). Here we evaluated the antitumor activities of sunitinib on orthotopic models of GBM in vitro and in vivo. Sunitinib potently inhibited angiogenesis that was stimulated by implantation of U87MG and GL15 cells into organotypic brain slices at concentrations as low as 10 nM. At high dose (10 μM), sunitinib induced direct antiproliferative and proapoptotic effects on GL15 cells and decreased invasion of these cells implanted into brain slices by 49% (p < 0.001). Treatment was associated with decreases in Src (35%) and focal adhesion kinase (44%) phosphorylation. However, anti-invasive activity was not observed in vivo at the highest dose level utilized (80 mg/kg per day). Survival experiments involving athymic mice bearing intracerebral U87MG GBM demonstrated that oral administration of 80 mg/kg sunitinib (five days on, two days off) improved median survival by 36% (p < 0.0001). Sunitinib treatment caused a 74% reduction in microvessel density (p < 0.05), an increase in tumor necrosis, and a decrease in number of GBM cells positive for MIB antibody. Sunitinib exhibited potent antiangiogenic activity that was associated with a meaningful prolongation of survival of mice bearing intracerebral GBM. These data support the potential utility of sunitinib in the treatment of GBM.